Effectiveness of ERAS Nursing Programe to Pain Level, Early Mobilization and Length of Stay for Patients Post Cholecystectomy Laparoscopy in Pluit Hospital, Jakarta - Nila Kumala Widjaya; Maria Astrid; Sutanto Priyo (Asian Journal of Social and Humanities, 2024)
Laparoscopic Cholecystectomy is method surgery to choice. With the ERAS, role of nurses is high to care the patient recovery after  surgery can reducing length of stay in hospital,  post operative hospitalization early mobilization and  level  pain have been proven. However, most studies have been  carried out in medical research. In this study,  we evaluated the efficacy of ERAS compared with control  perioperative period care for Laparoscopic Cholecystectomy. The research has been designed as a quasi-experiment one group control and group intervention. The study was conducted at Pluit Hospital, Jakarta from July-August 2023 on a total of 65 patients with 40  patients each in the ERAS  group and 25 patients control group. The main outcome was the length of hospital stay after surgery. The secondary outcomes Numeric Rating Scale (NRS) scores for post operative pain and early mobilization after surgery. The ERAS group was provided with perioperative education, pre operation 2 hours oral carbohydrates, intra operative insulation, early mobilization post operative, multimodal analgesia (colaborative intervention) and early activity. In the ERAS group Numeric Rating Scale after surgery was lower (1,87 vs 5,72, p value < 0,001), more earlier mobilization (3,45 hours vs 9,12 hours, p value < 0,001) and the length of hospital stay after surgery was shorter (27,13 hours vs 74,84 hours, p value < 0,001). Conclusion: Even the research in X hospital Jakarta, the use of the ERAS Nursing Programme concept for Laparoscopic Cholecystectomy surgery can reduce the length of hospital stay and lessen the pain of patients after surgery, early mobilization and accelerate post operative recovery.